2020
DOI: 10.3389/fninf.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

MonkeyCBP: A Toolbox for Connectivity-Based Parcellation of Monkey Brain

Abstract: Non-human primate models are widely used in studying the brain mechanism underlying brain development, cognitive functions, and psychiatric disorders. Neuroimaging techniques, such as magnetic resonance imaging, play an important role in the examinations of brain structure and functions. As an indispensable tool for brain imaging data analysis, brain atlases have been extensively investigated, and a variety of versions constructed. These atlases diverge in the criteria based on which they are plotted. The crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…2B). These results of validity indices suggested the consistency of the parcellations across subjects and the similarity of the topological organization distribution of the parcellation results between the bilateral hemispheres at the group level [42]. In addition, at the individual diffusion space level, the index results of PCA also suggested a segregation of the FPC into an average of 8 subdivisions for each of the hemispheres (left hemisphere, 8.31, see Fig.…”
Section: Connectivity-based Parcellation and Subregional Anatomical Cmentioning
confidence: 65%
See 3 more Smart Citations
“…2B). These results of validity indices suggested the consistency of the parcellations across subjects and the similarity of the topological organization distribution of the parcellation results between the bilateral hemispheres at the group level [42]. In addition, at the individual diffusion space level, the index results of PCA also suggested a segregation of the FPC into an average of 8 subdivisions for each of the hemispheres (left hemisphere, 8.31, see Fig.…”
Section: Connectivity-based Parcellation and Subregional Anatomical Cmentioning
confidence: 65%
“…However, in the current study, we mainly set two parameters (number of samples = 15000; step size = 0.2 mm), other parameters are based on the default values. All these parameters were based on previous studies [33,42] and the official instructions of FSL. Tournier et al have revealed that the dispersion in tractography is dependent on the step size; small step sizes reduce the spread of probabilistic tracking results [98].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are freely available to researchers, enabling larger multi-site studies. The PRIME-DE has been instrumental in leading this push towards openness and reproducibility in the macaque community (Milham et al, 2020), and data from the PRIME-DE has already been used in several studies (Froudist-Walsh et al, 2018;He et al, 2020;Heuer et al, 2019;Oligschläger et al, 2019;Valk et al, 2020;Xu et al, 2019bXu et al, , 2019aXu et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%